2022
DOI: 10.1002/hbm.26043
|View full text |Cite
|
Sign up to set email alerts
|

Tau as a biomarker of cognitive impairment and neuropsychiatric symptom in Alzheimer's disease

Abstract: The A/T/N research framework has been proposed for the diagnosis and prognosis of Alzheimer's disease (AD). However, the spatial distribution of ATN biomarkers and their relationship with cognitive impairment and neuropsychiatric symptoms (NPS) need further clarification in patients with AD. We scanned 83 AD patients and 38 cognitively normal controls who independently completed the mini‐mental state examination and Neuropsychiatric Inventory scales. Tau, Aβ, and hypometabolism spatial patterns were characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Unlike tau pathology, which is widely acknowledged for its association with clinical manifestation of AD, cortical amyloid accumulation shows a less robust association with cognitive or functional decline. 39 , 40 In this study, we observed only weak associations between blood-based Aβ42/40 ratio and memory and semantic fluency decline. A recent study similarly failed to evidence an association between plasma Aβ42/40 ratio and global cognitive decline.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Unlike tau pathology, which is widely acknowledged for its association with clinical manifestation of AD, cortical amyloid accumulation shows a less robust association with cognitive or functional decline. 39 , 40 In this study, we observed only weak associations between blood-based Aβ42/40 ratio and memory and semantic fluency decline. A recent study similarly failed to evidence an association between plasma Aβ42/40 ratio and global cognitive decline.…”
Section: Discussioncontrasting
confidence: 59%
“…Tau-PET imaging studies have consistently shown a correlation between the accumulation of neurofibrillary tangles and the clinical manifestation and progression of symptoms in AD. 39 , 40 The regional distribution of neurofibrillary tangles corresponds to deficits observed in specific cognitive domains. Recent studies have shown that, even when measured in blood, p-tau is associated with the cognitive manifestations of AD, 17 , 18 , 20 , 41 , 42 independent of confounding factors such as renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, blood levels of tau and p-tau differ significantly among individuals with cognitive impairments, traumatic brain injury (TBI), or COVID-19. The study by Dang et al [122] emphasizes the significant correlation between tau accumulation and cognitive decline, as well as neuropsychiatric symptoms, showcasing its diagnostic superiority over Aβ for distinguishing AD patients from cognitively normal controls. Notably, tau PET imaging demonstrates greater accuracy than Aβ in this differentiation, with pronounced tau deposition in the inferior temporal lobes strongly associated with the severity of cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%
“…AD is a dual proteinopathy (Aβ and Tau pathology). However, the load of misfolded Tau protein (Tau pathology) seems to be the critical factor in determining cognitive decline [18,19]. Like all proteins in a cell, the precise functions and localisation of Tau protein are dependent on its interaction with many other cellular proteins [20,21].…”
Section: Introductionmentioning
confidence: 99%